Dopamine-mediated volume transmission in midbrain is regulated by distinct extracellular geometry and uptake. - Cragg, S; Nicholson, C; Kume-Kick, J; Tao, L; Rice, M (2001)
Somatodendritic release of dopamine (DA) in midbrain is, at least in part, nonsynaptic; moreover, midbrain DA receptors are predominantly extrasynaptic. Thus somatodendritic DA mediates volume transmission, with an efficacy regulated by the diffusion and uptake characteristics of the local extracellular microenvironment. Here, we quantitatively evaluated diffusion and uptake in substantia nigra pars compacta (SNc) and reticulata (SNr), ventral tegmental area (VTA), and cerebral cortex in guinea pig brain slices. The geometric parameters that govern diffusion, extracellular volume fraction (alpha) and tortuosity (lambda), together with linear uptake (k'), were determined for tetramethylammonium (TMA(+)), and for DA, using point-source diffusion combined with ion-selective and carbon-fiber microelectrodes. TMA(+)-diffusion measurements revealed a large alpha of 30% in SNc, SNr, and VTA, which was significantly higher than the 22% in cortex. Values for lambda and k' for TMA(+) were similar among regions. Point-source DA-diffusion curves fitted theory well with linear uptake, with significantly higher values of k' for DA in SNc and VTA (0.08--0.09 s(-1)) than in SNr (0.006 s(-1)), where DA processes are sparser. Inhibition of DA uptake by GBR-12909 caused a greater decrease in k' in SNc than in VTA. In addition, DA uptake was slightly decreased by the norepinephrine transport inhibitor, desipramine in both regions, although this was statistically significant only in VTA. We used these data to model the radius of influence of DA in midbrain. Simulated release from a 20-vesicle point source produced DA concentrations sufficient for receptor activation up to 20 microm away with a DA half-life at this distance of several hundred milliseconds. Most importantly, this model showed that diffusion rather than uptake was the most important determinant of DA time course in midbrain, which contrasts strikingly with the striatum where uptake dominates. The issues considered here, while specific for DA in midbrain, illustrate fundamental biophysical properties relevant for all extracellular communication.